1992
DOI: 10.1093/bja/68.2.168
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine Green Clearance and Hepatic Function During and After Prolonged Anaesthesia: Comparison of Halothane With Isoflurane

Abstract: Specific biochemical and physiological tests of liver function were used to assess 20 consecutive patients undergoing prolonged head and neck surgery with halothane or isoflurane anaesthesia. Hepatic function was assessed by measurement of serum concentrations of total bilirubin and albumin, and plasma activity of pseudocholinesterase, gamma-glutamyl transferase (GGT), aspartate transaminase (AST), alkaline phosphatase (ALP) and hepatic glutathione S-transferase. Plasma clearance of indocyanine green was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 15 publications
1
21
1
1
Order By: Relevance
“…THBF in our patients was slightly less than has been reported in previous studies using ICG clearance and extraction in awake patients (14), and this may be related to anesthesia induction and maintenance (7). Liver blood flow values cannot be determined from studies that rely only on the rate of disappearance of ICG (22,23). Animal studies have indicated that halothane interferes with the capacity of the liver to metabolize certain drugs (24), including ICG (2), so the accuracy of using this dye to assess liver blood flow during inhaled anesthesia may be questionable.…”
Section: Resultscontrasting
confidence: 67%
“…THBF in our patients was slightly less than has been reported in previous studies using ICG clearance and extraction in awake patients (14), and this may be related to anesthesia induction and maintenance (7). Liver blood flow values cannot be determined from studies that rely only on the rate of disappearance of ICG (22,23). Animal studies have indicated that halothane interferes with the capacity of the liver to metabolize certain drugs (24), including ICG (2), so the accuracy of using this dye to assess liver blood flow during inhaled anesthesia may be questionable.…”
Section: Resultscontrasting
confidence: 67%
“…In contrast, GST-α has been found to be equally distributed in both these regions [4]. Centrilobular hepatocytes are very susceptible to damage in a variety of clinical conditions including allograft rejection [7], viral hepatitis [8], chronic active hepatitis [9] and hepatotoxicity [10].…”
Section: Introductionmentioning
confidence: 99%
“…The biggest exception to this compensatory response of most volatile anesthetics is halothane, which appears to lyse this reflex arc and causes a decrease in both PBF and HABF, 51 decreasing hepatic perfusion and worsening liver damage. 52 For this reason, halothane is not recommended for patients with liver disease. Newer volatile agents such as sevoflurane 53 and desflurane 54 appear to compare favorably with isoflurane, and a choice between these 3 volatile anesthetics may be made on factors other than hepatic protection.…”
Section: Intraoperative Anesthetic and Drug Administrationmentioning
confidence: 99%